Effects of melatonin on peritoneal fibrosis induced by high glucose peritoneal dialysis in rats - XING Bei-bei; ZHU Qi-jin; QI Xiang-ming; XU Xing-xin; WU Yong-gui (Linchuang shenzangbing zazhi)
Objective To investigate the effects of melatonin（MT） on peritoneal fibrosis induced by high glucose peritoneal dialysis in rats.Methods 38 SD male rats were randomly assigned into 5 groups:control group（n = 6）,peritoneal fibrosis group（n = 8）,peritoneal fibrosis ± MT 5 mg·kg-1 ·d-1 administration group（low MT dose group,n = 8）,peritoneal fibrosis ± MT 10 mg·kg-1·d-1 administration group（moderate MT dose group,n = 8）,peritoneal fibrosis ± MT 20 mg·kg-1 ·d-1 administration group（high MT dose group,n = 8）.The rats were injected intraperitoneal with4.25%peritoneal dialysis fluid at 100 ml·kg-1 daily to build peritoneal fibrosis model.After 28 days,4 h peritoneal equilibration test（PET） was carried out,measuring amount of ultrafiltration（UF）,and calculating both dialysate-to-plasma ratios（D/P） for creatinine at 4 h and the ratio of glucose at4 h to the dialysate glucose concentration at time zero（D/D0）.Rats were killed,taking the parietal peritoneum HE and Masson staining to observe the morphological changes of the peritoneum.We use immunohistochemical methods to detect the expressions of transforming growth factor β1（TGF-β1）,collagen Ⅰ（Col-Ⅰ） and orsmooth muscle actin（α-SMA）.Results（1） Compared with the control group,UF and D4/D0 were significantly decreased（P<0.05） and D/Purea was markedly increased（P<0.05） in model group;Compared with the model group,UF and D4/D0 were significantly increased（P<0.05） and D/Purea was markedly decreased（P<0.05） in MT groups.（2） In the control group,the peritoneal tissues had smooth surface,the visible flat mesothelial monolayer cells covered loose connective tissues;compared with the control group,the peritonea of the model group were markedly thickened,with rough surface,and mesothelial cells were swelling and lost with collagen deposition.All above mentioned pathological changes reduced markedly in MT groups.（3） Expressions of TGF-β1,Col-1 and α-SMA were significantly increased in model group than the control group（P<0.05）;they were significantly decreased by treatment with MT.Conclusions MT can inhibit peritoneal fibrosis in rats by improving the structure and function of the peritoneum and inhibiting the expressions of the TGF-β1,α-SMA and Col- Ⅰ.